Aspectos socioeconômicos, culturais e políticos da contribuição do campus IV da Universidade Estadual da Paraíba no município de Catolé do Rocha/PB - Forte, Danilo Cavalcante de Sousa (2020)
The expansion and interiorization of Higher Education Institutions (HEIs) have as main goal the democratization of this type of education through the expansion of their access to populations that are distant from larger urban centers. The role played by both federal and state HEIs was paramount in increasing the level of public and free education, with an emphasis on universities. In this context, this research has the general objective of analyzing the socio-economic, cultural, and political set of the foundation of Campus IV of Paraíba State University in Catolé do Rocha/PB municipality. The expansion and interiorization process of Paraíba State University occurred significantly since 2004, after achieving its financials autonomy. It is currently present in 8 campuses through Paraíba state, which may be inferred that it has changed the urban dynamics of these locations. In this context, it is possible to declare that the creation of campus IV streamlined a process of socioeconomic and cultural development in Catolé do Rocha municipality/PB. Thus, this research has the general objective of studying the socioeconomic, cultural, and political aspects of campus IV of Paraíba State University contributions in Catolé do Rocha municipality/PB, also having the specific objectives: a) to investigate the socioeconomic evolution in the territorial section of Catolé do Rocha/PB before and after the creation of UEPB campus IV; b) recover the memory features of the implantation of UEPB campus IV in Catolé do Rocha municipality/PB; c) to know the socio-economic and cultural changes in the municipality after the creation of campus IV, from the vision of UEPB's municipal and academic political leaders; d) investigate the actions and contributions of campus IV in the municipality in terms of employed resources, human resources training, teaching, research, and extension actions. The methodological scheme has used quantitative indicators collection (IDHM index; FIRJAN index; GINI coefficient; per capita income; employed persons; GDP; municipal collection; active companies and MEIs; and sectorial diagnosis of campus IV), in addition to field research with political leaders from the municipality and academics from UEPB (qualitative), through semi-structured interviews, having as variables: memory recovery from the creation of campus IV; the relationship between university interiorization and regional development; and perception of local effects of university interiorization. The main results indicated that campus IV presents a positive scenario in the socio-economic diagnosis given its territorial profile. UEPB has contributed, since its creation, to important social changes, resulting from its institutional actions (teaching, research, and extension), in addition to promoting the economy with resources from the payment of salaries and maintenance of the campus (R$ 11,760,908.36). It concluded that the presence of UEPB supported the economic development, the social, and cultural dynamics of Catolé do Rocha municipality/PB.